Analisis Strategi Pemasaran Terhadap Minat Nasabah Pada Bank Mandiri KC. Pematangsiantar - Junaidi Siahaan; Ompon Lastiur Sianipar; Sumaizar Sumaizar (Jurnal Akuntansi Dan Manajemen Indonesia (JAMIN), 2021)
The purpose of this study was to see the effect of the marketing mix strategy on customer interest. The formulation of the problem in this study is whether the Marketing Mix strategy has an effect on customer interest at Bank Mandiri KC Pematangsiantar. The purpose of this study is to determine whether the Marketing Mix has an effect on customer interest at Bank Mandiri KC Pematangsiantar. This research is included in the type of field research (field research) with descriptive nature using primary and secondary data, besides the data collection methods in this study use observation and interviews, and this analysis method uses quantitative analysis methods. Based on the results of this study indicate that the application of marketing strategies using the marketing mix, the products offered are very varied according to the needs of the community for the present and the future, then promotions use personal selling, advertising through television, brochures and others. , publicity with exhibition activities, social services. The marketing strategy that has been implemented has been good in increasing customer interest. From the results of data analysis, it can be concluded that, there is a significant positive effect between the marketing strategy variable (X) on customer interest (Y) at Bank Mandiri Kc Pematangsiantar, the contribution of the marketing strategy variable (X) on customer interest (Y) coefficient of determination (R2) of 0.76 indicates that 76% of marketing strategy (X) affects customer interest (Y), while 24% is influenced by other variables not discussed in this study.